ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UKUR EFEKTIVITAS KINERJA ARUS KAS PERUSAHAAN - Widyaningsih, Wit; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the stages of preparing cash flow statement and calculatingthe ratio analysis of cash flow statement to measure the effectiveness of financial performance of a company andto find out efforts that have to be carried out in order to increase the cash flow.This research is a qualitativedescriptive research that is meant to describe the condition that has occurred, to observe, to disclose, and toillustrate correctly things that are being handled and to make conclusion. The data analysis has been done byusing the ratio analysis of cash flow statement. The result of the calculation of cash flow statement and theanalysis of cash flow statement shows that the effectiveness of financial statement of PT Kembang BulanSurabaya in 3 year periods (2011-2013) shows less good financial performance, it can be seen from thecalculation of 2012 cash flow statement, the net cash of the operating activity shows the result is negative valueand the result of cash flow analysis ratio shows that the operating cash flow ratio in 2011-2013 periods is under1. The result of calculation ratio which shows negative value and operating cash flow ratio which is under 1describes that PT Kembang Bulan Surabaya is unable to meet its obligation and its commitments. This inabilityis caused by in 3 year periods (2011-2013) PT Kembang Bulan Surabaya has not presented their cash flowstatement and has not performed cash flow statement analysis so the financial performance cannot be knownearly to do some improvements particularly to improve the cash flow of the company.Keywords: Cash Flow Statement, Cash Flow Statement Analysis, and the Effectiveness of Cash Flow Statement